Origin of Colossal Dielectric Behavior In Double Perovskite Ba2CoNbO6. Issue 7 (15th April 2013) - Wang, Guojing; Wang, Chunchang; Huang, Shouguo; Lei, Changmei; Sun, Xiaohong; Li, Teng; Liu, Lina; Jones, J.
<x xml:space="preserve">Abstract</x> Ba2CoNbO6 ceramic samples were synthesized by solid‐state reaction technique. X‐ray photoemission spectroscopy reveals the coexistence of mixed‐valent structure of Co2+/Co3+ in the sample. Dielectric measurements reveal that the sample shows colossal dielectric behavior. This behavior is contributed by two thermally activated dielectric relaxations: the low‐temperature relaxation is a polaron relaxation resulting from the hopping motions of self‐trapped holes; the high‐temperature relaxation is a Maxwell–Wagner relaxation caused by the grain‐boundary response. Our results indicate a multirelaxation mechanism, i.e., the coupling of the polaronic relaxation and the Maxwell–Wagner relaxations might be a common origin of the colossal dielectric behavior found in different materials.